The unexpected for the expecting parent : effects of disruptive early interactions on mother–infant relationship - Wong, Keri Ka-Yee (2020)
High-quality parental caregiving promotes children’s development from their day of birth or even earlier. Whether there are ways to predict, and ultimately enhance, parental caregiving quality during the prenatal stages of development has been less well understood. This circumstance is even truer when things do not go according “to plan.” In this commentary, we explore two possible scenarios, perhaps unexpected for expectant parents, that can affect children’s development: (1) postpartum parental displays of atypical behaviors and parental caregiving strategies (i.e., maternal/paternal depression) and (2) postpartum child displays of atypical behaviors (i.e., autism spectrum disorder).